2014
DOI: 10.14260/jemds/2014/2747
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlation of Acute Appendicitis With Ultrasound Examination and Histopathology of Appendix

Abstract: Hernia is commonly operated in surgical department either emergency basis or as elective case. Unusual contents of hernia sac are uncommon, but are likely to be encountered by a surgeon in his career due to the frequency of hernia repair. The presence of vermiform appendix in inguinal hernias, referred to as Amyand's hernia, is rare occurring in about 1% of inguinal hernias. This is to present our experience of unusual contents in inguinal hernia sac. Amyand's hernia is not very often seen in the clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Shreshtha et al found USG to have a sensitivity of 85.7% and specificity of 88.2% in the diagnosis of AA with PPV of 96.4% and NPV of 62.5%( 16 ). Inamdar et al found the accuracy and sensitivity of USG in the diagnosis of AA to be 95% and 95.83% ( 17 ). In our study, the sensitivity, specificity, PPV, NPV, and accuracy were 70.73%, 83.33%, 90.62%, 55.56%, and 78.54, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Shreshtha et al found USG to have a sensitivity of 85.7% and specificity of 88.2% in the diagnosis of AA with PPV of 96.4% and NPV of 62.5%( 16 ). Inamdar et al found the accuracy and sensitivity of USG in the diagnosis of AA to be 95% and 95.83% ( 17 ). In our study, the sensitivity, specificity, PPV, NPV, and accuracy were 70.73%, 83.33%, 90.62%, 55.56%, and 78.54, respectively.…”
Section: Discussionmentioning
confidence: 99%